An introduction to the co-creation of policy briefs with youth and academic teams. Issue 1 (1st January 2023) - Dunlop, Lynda; Rushton, Elizabeth A. C.; Atkinson, Lucy; Blake, Celena; Calvert, Saul; Cornelissen, Eef; Dècle, Clémentine C. M.; DeSchrijver, Jelle; Dhassi, Kirndeep K.; Edwards, Rosalind P. R.; Malaj, Greta; Mirjanić, Jovana; et al.
ABSTRACT: Drawing on insights from a four-day online workshop, which explored geo-engineering and policy making with 13 youth participants, an academic and youth authorial team provide a guide to the co-creation of policy briefs. Drawing on excerpts from the policy brief at different stages of development and commentary provided by the authors during the workshops, we set out four stages including (1) Identifying the key message and audience, (2) Reading and critically engaging with examples of policy briefs during the drafting process, (3) Developing the policy brief text, and (4) Reviewing and revising the policy brief. We have developed this guidance with a co-creative, group work approach in mind and suggest that this has relevance for those working in and beyond the discipline of geography.